PENGARUH IKLIM ORGANISASI DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA HOTEL ASANA AGUNG PUTRA BALI - Lestari Putra, I Gusti Ayu Yuliana; Sudharma, I Nyoman (E-Jurnal Manajemen; Vol 5 No 9 (2016), 2016)
This research is based on the premise that every organizations both government and private sectors have a goal to be achieved. Human Resource Management requires open communication and relationships within the boundaries, authority and responsibility. The existence of this conflict can also affect the job satisfaction of employees, which in turn leads to the employee Job Stress. This research was conducted at the Hotel Asana Agung Putra Bali. The respondents as much as 49 employees, with the census or sampling methods saturated. Data collected through questionnaires using Likert scale. The analysis technique used is the Multiple Linear Regression. Based on the results of research conducted found that the influence of organizational climate is positive dan significant effect on job satisfaction. Work stress is negative and significant effect on employee job satisfaction.
Keywords: organizational climate, job stress, job satisfaction